The Relationship Of Leg Muscle Power To Lay-up Skills In Jabar XIII POPDA Basketball Players, Karawang District - Muhammad Fariz Ghazi Syaiffudin; Dany Aulia; M. Arief Setiawan; Habibi Hadi Wijaya (UNIVERSITAS NEGERI MAKASSAR, 2024)
Based on the analysis that the authorities saw on the POPDA XII JABAR 2023 most teams entering points is using lay-up skills. Data analysis is a technique of processing data from the results of research data. Then the data is processed and analyzed to test the research hypothesis. Once the test scores have been obtained, the scores are compiled, processed, and analyzed. So from that the researchers chose to use three tests, that is, there is a normality test with Kolmogorov Smirnov, then there's a correlation test and the last one uses a hypothetical test to find the hypothesis of the research. And it can be said that from the data results of this test, there is a relationship. And the last test results of the hypothesis then it is known that the value of the significance of the power of the body muscle against the skill lay-up is 0.733 which means it is not equal to 0 and means it has a strong relationship because with the sum of values between 0.600 – 0.799. Reviewed from the analysis of data above this study can be taken the presentation and the results that are already visible, the conclusion of this study is there is a significant relationship between the power of the muscle branch with the lay-up skills of the POPDA Basketball player Karawang district, with the results of a strong link.